2015
DOI: 10.7324/japs.2015.50808
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in-vivo antiarthritic potential of methanolic extract of Costus speciosus rhizome

Abstract: Objective: To evaluate anti-arthritic potential of methanolic extract of rhizome of Costus speciosus Koen. Methods: The powdered drug was extracted with 80% methanol. The crude extract was subjected to phytochemical investigation and was evaluated for its anti-arthritic potential by freund's complete adjuvant induced arthritis model in adult wistar albino rats. Determination of different parameters like arthritic score, arthritic index, paw thickness, body weight, and pain, altered liver enzymes and biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Drug was administered orally to overnight fasted rat sat a volume of 1 ml/100 g body weight. Erdosteine was dissolved in DMSO and was administered at a single dose of 2000 mg/kg [17] in Group B and tap water was administered to (Fig. 2) Group A and food was withheld for another 3 h. They were observed continuously for 4 h for behavioral and autonomic profiles and regularly for the first critical 24 h and daily for a total of 14 days for any lethality.…”
Section: Acute Oral Toxicity Studymentioning
confidence: 99%
“…Drug was administered orally to overnight fasted rat sat a volume of 1 ml/100 g body weight. Erdosteine was dissolved in DMSO and was administered at a single dose of 2000 mg/kg [17] in Group B and tap water was administered to (Fig. 2) Group A and food was withheld for another 3 h. They were observed continuously for 4 h for behavioral and autonomic profiles and regularly for the first critical 24 h and daily for a total of 14 days for any lethality.…”
Section: Acute Oral Toxicity Studymentioning
confidence: 99%
“…In another study [12], Animal Wistar albino rat (150-200 g) of either sex. Optimum condition-temperature -25°C±0.5°C Relative humidity -55-65.…”
Section: Plant Detailsmentioning
confidence: 99%
“…Here, in the study, they showed that plant has ability to decrease the TNF-α level. Hence, we may say that the plant has immunosuppressive effect [12].…”
Section: Plant Detailsmentioning
confidence: 99%
“…After 6 hours of test administration the animals weighed again. A careful clinical examination was made once in each day for next 14days (OECD 4/26, 2006) [9].…”
Section: Acute Oral Toxicity Study (Ld50)mentioning
confidence: 99%